Analysis of Ferric Protoporphyrin IX Effects on Human Platelets: Hematin Is a More Potent Agonist than Hemin - Diana M. Mikhailova; Julia Sudnitsyna; Polina Kovgan; Lidia Naida; Alexandra Kharazova; Igor Mindukshev; Stepan Gambaryan (Cells)
Hemolysis during severe diseases (malaria, hemorrhagic stroke, sickle cell disease, etc.) and blood transfusion induces the release of free hemoglobin, which degrades to highly reactive and toxic compounds—hemin and hematin. Oxidized heme derivatives induce platelet activation, aggregation, and degranulation, leading to prothrombotic and inflammatory events. In the present study, we showed that hematin is a more potent agonist of platelet activation than hemin, and using several methods, including the original laser diffraction method, flow cytometry, and confocal microscopy, we demonstrated that hematin at low doses induces platelet activation and aggregation without reducing cell viability and affecting calcium efflux. On the contrary, hematin at high concentrations triggered phosphatidylserine exposure, severe loss of platelet viability, and calcium dysregulation, which was not inhibited by cGMP/PKG and cAMP/PKA pathways. Additionally, we showed that albumin could initiate disaggregation processes in hematin-activated platelets.